Financial Inclusion and Human Development: A Comparative Analysis of MENA and BRICS - Eid, Mohammad (AUC Knowledge Fountain, 2024)
Various efforts to enhance human development in several countries has been underway for years now, but the level of human development attained by countries in BRICS and MENA regions vary. This study empirically examines the role of financial inclusion and its impacts on human development; it investigates whether financial inclusion can be used to drive human development by examining and comparing its results in MENA and BRICS countries. The dependent variable is the score of Human Development index HDI. This study provides a unique comparative analysis of the role of financial inclusion and its effects on human development in MENA and BRICS countries. Data obtained includes the Financial Inclusion Index (Findex) of the World Bank and the Human Development Index (HDI) from the United Nations Development Program UNDP for 19 MENA countries and the original 5 BRICS countries. The data is obtained from the World Bank database (World Bank, 2021; https://www.worldbank.org/en/publication/globalfindex/Data) covering the period 2011-2021. The estimation method employed is Panel GMM EGLS accounting for cross-section weights. Results show that percentage of the adult population used a credit card demonstrate a significant negative impact on HDI, and percentage of the adult population borrowed from a formal financial institution shows a significant positive impact on HDI scores in MENA and BRICS countries. This study provides valuable insights to policy makers as they can draw on country specific dynamics to understand how to efficiently promote and tailor financial inclusion efforts to enhance human development.